Springs in the upper Drzewiczka catchment - Tomalski, Przemysław; Badowski, Radosław (Acta Geographica Lodziensia, 2024)
The aim of the study was to identify springs in the upper Drzewiczka catchment. It was carried out using detailed crenological mapping. Each one’s efficiency and basic physical properties of water (conductivity, temperature) were measured. The type of springs, morphological location, hydrogeological type, method of outflow and type of aquifer were also determined. In the upper Drzewiczka catchment, 74 springs were identified. Fifteen percent of the outflows are ascending. Five springs were selected from this group and were then observed every two weeks for a year. Discharge of the observed springs reaches its maximum at the transition of December to January. There is also a secondary maximum in April. The minimums occur in January and October.